Investigation of electromagnetic shielding properties of needle-punched nonwoven fabrics with stainless steel and polyester fiber - BEYİT, ALİ; SANCAK, ERHAN; USTA, İSMAİL; ÖZEN, MUSTAFA SABRİ (SAGE PUBLICATIONS LTD, 2013)
In this study, electromagnetic shielding properties of needle-punched nonwoven fabrics were investigated. The paper evaluates and compares the electromagnetic shielding of needle-punched nonwoven fabrics produced from stainless steel/polyester and normal polyester fibers. Stainless steel/polyester fiber and normal polyester fiber were blended at specified ratios in the experimental study. Webs were produced from the fibers with the carding machine and then bonded with the needle-punching machines. The thickness and electromagnetic shielding properties of the needle-punched fabrics were tested. An electromagnetic shielding effectiveness (EMSE) device was used for measuring the electromagnetic shielding. The experimental study indicated that as the conductive stainless steel fiber ratio in nonwoven fabrics increases, the EMSE also increases at low, medium and high frequencies. Satisfactory electromagnetic shielding values were obtained at wide bandwidth, i.e. 1200-3000 MHz. The highest EMSE values of the needle-punched nonwoven fabric with 25% conductive steel fiber were, respectively, 6 dB at 0-300 MHz low frequency, 12 dB at 300-1200 MHz medium frequency and 18 dB at 1200-3000 MHz high frequency. It was found that 90% of electromagnetic waves were shielded by nonwoven fabric at high frequencies, 85% at medium frequencies and 80% at low frequencies.
Keywords: nonwoven; stainless steel; polyester fiber; needle-punched fabric; electromagnetic shielding; COMPOSITES